2014
DOI: 10.1371/journal.pone.0088334
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphisms of MUC16 (CA125) and MUC1 (CA15.3) in Relation to Ovarian Cancer Risk and Survival

Abstract: ObjectiveTo examine single nucleotide polymorphism (SNPs) in MUC16 (CA125) and MUC1 (CA15.3) in relation to ovarian cancer risk and survival.MethodsWe genotyped germline variants of MUC16 (rs2547065, rs1559168, rs12984471, rs2121133) and MUC1 (rs2070803, rs4072037, rs1045253) using samples collected from 758 ovarian cancer cases and 788 controls enrolled in the New England Case-Control Study between 2003 and 2008. We calculated age-adjusted odds ratios (OR) and 95% confidence intervals (CIs) for disease risk u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 38 publications
0
13
0
Order By: Relevance
“…The serum CA125 was considered to be the most effective tumor marker for EC but have poor diagnostic sensitivity. [10][11][12] Besides CA125, EC also could be diagnosed by elevated levels of HE4, CA724, and CA19-9, each with their own unique advantages. [13][14][15] In our test, we detected serum level of HE4, CA125, CA724, and CA19-9 in 105 patients with EC; the results showed that the level of tumor markers was obviously higher in the EC group than that in the healthy controls.…”
Section: Discussionmentioning
confidence: 99%
“…The serum CA125 was considered to be the most effective tumor marker for EC but have poor diagnostic sensitivity. [10][11][12] Besides CA125, EC also could be diagnosed by elevated levels of HE4, CA724, and CA19-9, each with their own unique advantages. [13][14][15] In our test, we detected serum level of HE4, CA125, CA724, and CA19-9 in 105 patients with EC; the results showed that the level of tumor markers was obviously higher in the EC group than that in the healthy controls.…”
Section: Discussionmentioning
confidence: 99%
“…Many reports have focused on the diagnostic value of CA125 in ovarian cancer, and have advocated for increased use of serum CA125 in primary care as means of increasing detection of ovarian cancer [ 3 , 4 ]. CA125 is member of the tethered human mucus (MUC) family of large, heavily glycosylated transmembrane proteins that have a diverse range of functions [ 5 ]. The extracellular region of MUC16, which is over-expressed in epithelial ovarian carcinoma, is cleaved from the cell surface and circulates in the blood.…”
Section: Introductionmentioning
confidence: 99%
“…A recent large metaanalysis study of 6,580 gastric cancer cases and 10,324 controls including both Asian and European populations showed that G allele of rs4072037 polymorphism was associated with decreased risk of gastric cancer (OR = 0.72) (Zheng et al, 2013). Recent publications showed that genetic variation of MUC1 may be associated with ovarian cancer (Williams et al, 2014) and esophageal cancer (Palmer et al, 2012). In the only case-control study including CRC patients (Li et al, 2012c) rs4072037 showed a marginal association in Chinese population (OR 0.69,P=0.06).…”
Section: Discussionmentioning
confidence: 99%